Physiotherapist Perception of Best Practice in Managing Sacroiliac Joint Dysfunctions in Private Clinical Settings - S, Siva Kumar; Arun, Balasuburamaniam (Journal of Liaquat University of Medical & Health Sciences, 2020)
OBJECTIVE: To examine the best practice by physiotherapist in managing sacroiliac(SI) joint dysfunctions in private clinical settings. METHODOLOGY: The study was conducted in various physiotherapy clinics (25) involving 40 physiotherapists working more than 5 years. A qualitative, descriptive focused ethnographic approach was used to explore the physiotherapist perception of best practice in patient with SI dysfunctions at private clinical setting. Snowball sampling method was used to recruit sample physiotherapists, interviews were conducted in person by the two investigators. 40 physiotherapists were interviewed and the recordings were analyzed by the transcriber, the questions were focused on the various themes which were created by the authors. Themes include 1; Choice of modalities 2; Patient center care 3; Resource utilization 4; Inter professional consultation 5; Referral pattern followed by the clinical therapists. RESULTS: It was found that most of the clinical physiotherapists choose TENS as one of the pain relieving modality for the SI joint dysfunctions. CONCLUSION: This study findings highlights that private clinical physiotherapists were perceived the best practice for the patients with SI joint dysfunction and they do the best treatment for their patients. Keywords: Best practice for SI Joint dysfunction, Clinical physiotherapists, Private clinical therapists, TENS.